2009
DOI: 10.1038/ncb1915
|View full text |Cite
|
Sign up to set email alerts
|

The CDK4–pRB–E2F1 pathway controls insulin secretion

Abstract: CDK4-pRB-E2F1 cell-cycle regulators are robustly expressed in non-proliferating beta cells, suggesting that besides the control of beta-cell number the CDK4-pRB-E2F1 pathway has a role in beta-cell function. We show here that E2F1 directly regulates expression of Kir6.2, which is a key component of the K(ATP) channel involved in the regulation of glucose-induced insulin secretion. We demonstrate, through chromatin immunoprecipitation analysis from tissues, that Kir6.2 expression is regulated at the promoter le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
126
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(143 citation statements)
references
References 29 publications
14
126
1
2
Order By: Relevance
“…We also observed increases in Kir6.2 (also known as Kcnj11) expression in p-Rb and p-DKO mice, which is well known for regulation in insulin secretion and has also been implicated in beta cell proliferation, consistent with its regulation by E2F1 (ESM Fig. 3c) [32,33]. These results show intricate regulation of p53 by Rb family proteins and the fine-tuning of intracellular signalling that is potentiated by Rb and p107.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…We also observed increases in Kir6.2 (also known as Kcnj11) expression in p-Rb and p-DKO mice, which is well known for regulation in insulin secretion and has also been implicated in beta cell proliferation, consistent with its regulation by E2F1 (ESM Fig. 3c) [32,33]. These results show intricate regulation of p53 by Rb family proteins and the fine-tuning of intracellular signalling that is potentiated by Rb and p107.…”
Section: Resultssupporting
confidence: 75%
“…Persistently increased apoptosis with a concomitant reduction in proliferation resulted in net loss of beta cell mass in p-DKO mice with ageing, leading to the loss of improved glucose homeostasis observed in young p-DKO mice. Moreover, E2F1 has previously been shown to be involved in early pancreas development [40], insulin secretion [33,41] and proliferation [41][42][43][44]. These data show the importance of the precise regulation of E2F in determining the various biological outcomes of islets.…”
Section: Discussionmentioning
confidence: 65%
“…Also, they demonstrated that the CDK4-pRB-E2F1 pathway could be regulated by insulin signaling in mouse pancreatic islets (Annicotte et al 2009). This observation could explain in part why beta-cells from suckling rats show low proliferation rates (tested by Ki67 immunofluorescence, data not shown) despite their high expression of cell-cycle-related genes, indicating that the beta-cells' proliferative capability is inversely correlated with the basal robust insulin secretion and the glucosestimulated insulin secretion functions.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the CDK4-RB-E2F axis and other cell cycle components have acquired a main role in the control of insulin secretion by pancreatic β-cells [2,3], of oxidative metabolism [4] and of adipogenesis [5][6][7][8].…”
Section: Commentarymentioning
confidence: 99%